Studi Komparatif Pemikiran Filsafat Politik Ali Abdul Raziq dan Rashid Rida mengenai Khilafah - Unsi Andal Bara; Muliadi Muliadi; Iu Rusliana (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This article aims to explain the comparison of political philosophy thoughts, especially regarding the caliphate of two Muslim intellectual figures from Egypt who lived in the same period. Ali Abdul Raziq and Rashid Rida, these two figures talked about the formulation of the ideal state form for Muslims and the implementation of Islamic government. The author writes down the arguments of the two figures and then compares them with the formulations of the two. Khilafah which is a system of government that follows the leadership of the Prophet Muhammad, sharia as the legal basis and Islam as an ideology in running the government. This type of research is library research by applying the comparative method, which prioritizes library materials as the main source. The results of the research from the two Muslim intellectual works from Ali Abdul Raziq's book entitled al-Islam wa Usul al-Hukm and the book Al-Khilafah wa Al-Imamah written by Rashid Rido, show that there are very basic differences in the thoughts of the two figures, where Rashid Rida firmly held the position that followers of Islam are required to uphold the caliphate in their country based on sharia and ijma. On the other hand, Ali Abdul Raziq argues that there is no binding obligation for Muslims to establish a caliphate in their country, he argues that Muslims are free to choose what ideology will be applied in a country. Because in the Qur'an and as-Sunnah do not regulate the form of state that Muslims must apply. The thought of Islamic political philosophy, of course, does not only come from these two figures, many Muslim intellectuals argue that this matter needs to be explored for the benefit of Muslims in terms of the state.